If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-r-3(r-1)=0
We simplify the equation to the form, which is simple to understand
-r-3(r-1)=0
Reorder the terms in parentheses
-r+(-3r+3)=0
Remove unnecessary parentheses
-r-3r+3=0
We move all terms containing r to the left and all other terms to the right.
-1r-3r=0-3
We simplify left and right side of the equation.
-4r=-3
We divide both sides of the equation by -4 to get r.
r=0.75
| 7p+3q=4 | | -7(5x-3y+5)= | | 17=4-7x-8 | | 3p+4q=26 | | 9w+w+6w= | | 5k-37=11(k+1) | | 71-6v-10v+32=-4v+7 | | (3+6)=3+(6) | | 5x+56+2x+82=180 | | 10v^3=90v | | 4h-7=12h+9 | | -2(5p+3)-3(p-6)= | | 2Y*3Y= | | 4d-5=-5 | | 5x+16+2x+82=180 | | -3x-9=-33 | | 6(2x-5)-4(x+2)-17x= | | 8x+27=5x+63 | | 2c-8=8 | | 16-32-2= | | (8+6)+4=8+(6+4) | | 2y-(-3)=-17 | | -16+-32-2= | | 8x-22=2x+4 | | 2v-(10)=16 | | 4y-5=9y+15 | | 3p-7=6p+8 | | -12m=-18 | | 40-3x-12=44+5x | | -3z-(10)=-17 | | 3x+5=-21-5-x | | 12j^2+11j=-2 |